ORGANIZACIÓN CONTABLE EN LA EMPRESA COMERCIAL DE LA SRA. DARQUEA SÁNCHEZ MARÍA CECILIA DE LA CIUDAD DE LOJA, PERÍODO DEL 01 DE ABRIL AL 30 DE JUNIO DEL 2023. - Herrera Herrera, Janina del Carmen (2024)
The Curricular Integration Work called “Accounting organization in the commercial Company of Mrs. Darquea Sánchez María Cecilia from the city of Loja, period from April 1 to June 30, 2023.” was developed taking into account the commercial company’s need to gather, organize and record all information of its economic movements in an effective and efficient manner, allowing to obtain real information of the economic and financial situation while simultaneously meeting each one of the proposed specific objectives. The work was carried out through the execution of a plan and manual of accounts specially adapted to the needs and activities of the company. To achieve this, accounts were established within the categories of assets, liabilities, patrimony, income, costs and expenses, each with its own codification and detailed description, this allowed an efficient location of the accounts during the entire accounting process; an initial inventory was elaborated through the physical verification of the properties, values, rights and obligations to show the assets, liabilities and patrimony of the company. The respective auxiliary records were designed, such as sales records detailing the payment method for sales, whether in cash, credit, accounts payable or through bank transactions; payment roles were created detailing the incomes and expenses received monthly by each employee and the role of provisions containing the provisions for each employee for social benefits, which facilitate the simplification of operational movements of the Commercial Company. The accounting process was carried out through the permanent inventory control system; in which it was necessary to create an Initial Inventory of all assets, rights, values and obligations, followed the Initial Situation Statement was prepared, which reflects the Assets, Liabilities and Patrimony at the beginning of the operational activities, then the Daily Book was made where the daily operations were registered, next the General Book was elaborated where each one of the accounts is detailed in an organized manner and with the respective balances, the Trial Balance 5 was prepared, which summarizes and verifies the equality of debit and credit balances, then, the Worksheet was prepared with the respective adjustments and closing of books, the Statement of Results which contains the incomes, costs and expenses, the Statement of Financial Position containing the assets, liabilities, patrimony and profit at the end of the financial year, the Cash Flow Statement showing the cash originated and applied during a period by the company in operating, investment and financing activities, thus providing information on the real, economic and financial situation of the Company.